Pediatric febrile urinary tract infections: the current state of play - Hewitt Ian K; Montini Giovanni (BMC, 2011)
Abstract Studies undertaken in recent years have improved our understanding regarding the consequences and management of febrile urinary tract infections (UTIs), which are amongst the most common serious bacterial infections in childhood, with renal scarring a frequent outcome. In the past pyelonephritic scarring of the kidney, often associated with vesico-ureteral reflux (reflux nephropathy) was considered a frequent cause of chronic renal insufficiency in children. Increasing recognition as a consequence of improved antenatal ultrasound, that the majority of these children had congenital renal hypo-dysplasia, has resulted in a number of studies examining treatment strategies and outcomes following UTI. In recent years there is a developing consensus regarding the need for a less aggressive therapeutic approach with oral as opposed to intravenous antibiotics, and less invasive investigations, cystourethrography in particular, following an uncomplicated first febrile UTI. There does remain a concern that with this newer approach we may be missing a small subgroup of children more prone to develop severe kidney damage as a consequence of pyelonephritis, and in whom some form of intervention may prove beneficial. These concerns have meant that development of a universally accepted diagnostic protocol remains elusive.